SWOT SEBAGAI STRATEGI MENINGKATKAT DAYA SAING BISNIS TOKO SOUVENIR - Gaspers, Susan; Dedi, Selmi; Sudarwadi, Dirarini (Cakrawala Management Business Journal, 2025)
This study aims to determine the Strength, Weaknesses, Opportunity and Treath (SWOT) analysis as a strategy to increase competitiveness at Souvenir Shop. In this study, the author uses a mix method, which is a method that combines quantitative and qualitative methods to be used together in one research activity. The results of the study indicate that the Internal Strategic Factors Analysis Summary (IFAS) matrix has good Strength and the External Strategic Factors Anallysis Summary (EFAS) has good Opportunity. The results of the IFAS and EFAS matrices show that the Souvenir Shop is in Quadrant I (Aggressive) which indicates that the Souvenir Shop has an opportunity where the Souvenir Shop is in a strong condition so that it is able to increase growth and acchieve maximum progress. The Souvenir Shop has good strengths that can be utilized as opportunities to increase product sales volume.